Multi-genome Scaffold Co-assembly Based on the Analysis of Gene Orders and Genomic Repeats - Aganezov, Sergey; Alekseyev, Max A. (Bioinformatics Research and Applications, 2016)
Advances in the DNA sequencing technology over the past decades have increased the volume of raw sequenced genomic data available for further assembly and analysis. While there exist many software tools for assembly of sequenced genomic material, they often experience difficulties with reconstructing complete chromosomes. Major obstacles include uneven read coverage and long similar subsequences (repeats) in genomes. Assemblers therefore often are able to reliably reconstruct only long subsequences, called scaffolds. We present a method for simultaneous co-assembly of all fragmented genomes (represented as collections of scaffolds rather than chromosomes) in a given set of annotated genomes. The method is based on the analysis of gene orders and relies on the evolutionary model, which includes genome rearrangements as well as gene insertions and deletions. It can also utilize information about genomic repeats and the phylogenetic tree of the given genomes, further improving their assembly quality.